2012
DOI: 10.5194/acp-12-11985-2012
|View full text |Cite
|
Sign up to set email alerts
|

Asian dust storm observed at a rural mountain site in southern China: chemical evolution and heterogeneous photochemistry

Abstract: Abstract. Heterogeneous processes on dust particles are important for understanding the chemistry and radiative balance of the atmosphere. This paper investigates an intense Asian dust storm episode observed at Mount Heng (1269 m a.s.l.) in southern China on 24-26 April 2009. A set of aerosol and trace gas data collected during the study was analyzed to investigate their chemical evolution and heterogeneous photochemistry as the dust traveled to southern China. Results show that the mineral dust arriving at Mt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 43 publications
0
45
1
Order By: Relevance
“…A number of studies in China reported that dust particles significantly enhanced the formation of sulfate and nitrate when dust plumes advected over urban areas (Li and Shao, 2009;Li et al, 2014;Nie et al, 2012;Qi et al, 2006;Sheng et al, 2003;Wang et al, 2013;Zhao et al, 2011Zhao et al, , 2007, which is very different from the conclusions of this study. We carefully examined the available meteorological records for the dust episodes in those studies.…”
Section: Intercomparisons and Implicationscontrasting
confidence: 89%
See 3 more Smart Citations
“…A number of studies in China reported that dust particles significantly enhanced the formation of sulfate and nitrate when dust plumes advected over urban areas (Li and Shao, 2009;Li et al, 2014;Nie et al, 2012;Qi et al, 2006;Sheng et al, 2003;Wang et al, 2013;Zhao et al, 2011Zhao et al, , 2007, which is very different from the conclusions of this study. We carefully examined the available meteorological records for the dust episodes in those studies.…”
Section: Intercomparisons and Implicationscontrasting
confidence: 89%
“…In many cases, dust was observed in cyclonic disturbances with weak fronts or without fronts (Cao et al, 2003;Nie et al, 2012;Wang et al, 2013). Cold fronts could not be confirmed clearly at places of dust arrival in those studies.…”
Section: Intercomparisons and Implicationsmentioning
confidence: 66%
See 2 more Smart Citations
“…These compounds are very hygroscopic and thus may take up water vapor, forming a liquid phase on the dust surface even under the low-RH conditions of the dust storm period (RH = 22 ± 3.5%, Table 1). The aqueous phase is favorable for the formation of NH 4 NO 3 , which is probably formed via a gas-phase homogeneous reaction of nitric acid with ammonia and a subsequent partitioning into the liquid phase (Nie et al, 2012;Pathak et al, 2011). In addition, NO − 3 can also be produced in the liquid phase via heterogeneous reactions of gaseous HNO 3 , N 2 O 5 and NO x with dust particles (Finlayson-Pitts et al, 2003;Hanisch and Crowley, 2001;Laskin et al, 2005;Usher et al, 2003) Figure 12.…”
Section: Chemical Forms Sources and Productions Of Nitrate And Sulfatementioning
confidence: 99%